SISTEM PENDIDIKAN DI NEGARA AUSTRALIA - Abdul Wahab Syakhrani; Annisa, Evi, Fitri Hidayati, Hairin Nisa (CV. ADIBA ASIHA AMIRA, 2022)
That education in Australia actually begins with private educational institutions managed by non-government. This is understood because schools with non-state status are a very important part of the system. Education is organized based on community needs. As society develops, education must be encouraged to answer the needs of society. the development of education in Australia is left to each school to develop its education, adapted to the needs of the education community in Australia supported by a community that wants to preserve culture. Australia can organize education well. From a geographical perspective, in terms of education law, Australia is committed to providing quality and equitable education. The people of this country also agreed to guard and support quality education. From an economic perspective, Australia has proven that by investing in quality education, the Australian workforce is able to survive and this country is declared a competent country in the economic field.